Removal of Heavy Metals from Industrial Wastewater by Using RO Membrane - Algureiri, Ahmed H.; Abdulmajeed, Yossor R. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Industrial wastewater containing nickel, lead, and copper can be produced by many industries. The reverse osmosis (RO) membrane technologies are very efficient for the treatment of industrial wastewater containing nickel, lead, and copper ions to reduce water consumption and preserving the environment. Synthetic industrial wastewater samples containing Ni(II), Pb(II), and Cu(II) ions at various concentrations (50 to 200 ppm), pressures (1 to 4 bar), temperatures (10 to 40 oC), pH (2 to 5.5), and flow rates (10 to 40 L/hr), were prepared and subjected to treatment by RO system in the laboratory. The results showed that high removal efficiency of the heavy metals could be achieved by RO process (98.5%, 97.5% and 96% for Ni(II), Pb(II) and Cu(II) ions respectively). The permeate flux for all H.M ions was ranged between (10 to 56 L/m2.hr). The low level of the heavy metals concentration in the permeate implies that water with good quality could be reclaimed for further reuse. The RO membrane is characterized by very high efficiency as the H.M. ions removal of up to (97%) with good productivity and medium pressure that means a medium cost of the RO system.